The diagnosis of epilepsy - Von Meduna, Ladislaus (1939)
13 epileptics, 17 schizophrenics, five paralyzed and several classifiable patients in other psiconosográficos groups were tested against provocation diagnosed seizures by injecting Cardiazol to check if the seizure threshold versus Cardiazol is epileptic lower than in patients suffering from other mental illnesses. The xperiences were conducted so that by means of a prior anticonvulsant therapy sought to reduce the degree of each patient ietafinidad. The experiences provided the following specific results: it was found that in our case, the threshold of epileptic seizures is below 0.5 gr. of Cardiazol, whereas the non-epileptic is above this dose. Epileptic seizures caused by Cardiazol resemble the most frequent spontaneous attack experienced by the patient. When a patient twilight states, the Cardiazol in right dose of applicable threshold wakes twilight states, in a case dominated was achieved through metrazolic seizures, breaking into an epileptic serious twilight state which persisted for about two months . In 2 cases the verification of a high seizure threshold could be valued as evidence that invalidated the claim of the respective patient, suffering from epilepsy. The small number of patients studied does not allow to draw absolute scientific conclusions from what has just been exposed. Anyway I maintain that you can say with authority that if there are other syndromic clinical symptoms, testing a seizure threshold below 0.5 gr. of Cardiazol can dispel doubts about the diagnosis to make.